ANALYSIS OF SERVICE QUALITY FOR HEALTH SOCIAL SECURITY ADMINISTERING AGENCY (BPJS) USERS AT THE REGIONAL GENERAL HOSPITAL (RSUD) DR. SUHATMAN, MARS DUMAI CITY - Radha Kurnia; Sitti Rahmah (Yayasan Wayan Marwan Pulungan, 2024)
This research was motivated by complaints from patients using BPJS Health that the author found at the Regional General Hospital (RSUD) Dr. Suhatman, MARS Dumai City who were not satisfied with the health services provided by officers, so this research aims to analyze the quality of service for users of the Health Social Security Administering Body (BPJS) at the Regional General Hospital (RSUD) dr. Suhatman, MARS Dumai City. The method used is qualitative and is explained descriptively. The data sources used in this research are primary data and secondary data. The techniques used in collecting data are observation, interviews, and documentation, and then analyzed using an interactive model. Miles and Huberman, this model starts from collecting raw data, displaying data, reducing data, and arriving at data verification and conclusions. There were 10 informants interviewed in this study, namely 4 officers and 6 BPJS Health patients. The results of this research based on Tangibles, Reliability, Responsiveness, Assurance, and Empathy are classified as